Foundations of education - Zulueta, Francisco M.; Maglaya, Elda M. (Mandaluyong City, Philippines : National Book Store, 2004)
There are various definitions of education, but the best perhaps is that, education is changed for the better. A person may learn a wide range of knowledge, but if this knowledge does not change him into a better person, than inferentially he has not acquired education. The ultimate goal of education, therefore, is to change man to become better mentally, physically, socially and emotionally.
Preface -- PART ONE: HISTORICAL FOUNDATION. -- 1- Historical foundations of education -- 2- The Nature and development of Philippine nationalism -- PART TWO: ANTHROPOLOGICAL FOUNDATIONS -- Anthropology as a science -- 4- Culture -- 5- Communication -- 6- The Arts -- PART THREE: PHILOSOPHICAL FOUNDATIONS -- 7- Scope of philosophical foundations -- 8- The Educational philosophies of the world's greatest philosophers -- 9- Classical and contemporary philosophies -- PART FOUR: LEGAL FOUNDATIONS -- 10- Legal bases of education -- 11- Educational development decree of 1972 -- PART FIVE: PSYCHOLOGICAL FOUNDATIONS -- 12- The Psychological basis of education -- 13- Motivation -- 14- Learning and information processing -- 15- Personality -- PART SIX: SOCIOLOGICAL FOUNDATIONS -- 16- Social institution -- 17- Social process -- 18- Social problems -- 19- Leadership and public relations -- 20. Graft and corruption: its nature and origin -- 21- Values education
Includes bibliographical references.
Keywords: EDUCATION